Decision support system based in AHP method to selection vendors of clinical laboratorys inputs - Longaray, André Andrade (2019)
In a competitive marketing scenario, the purchasing area contributes significantly to the achievement of organizational goals. Its mission is to identify the competitive needs of products and services, becoming responsible for the timely delivery, costs optimization and quality. Within shopping, a correct selection of vendors is important for this to happen. From this perspective, the present study aims to develop a model that assists in the vendors’ selection process. This way, a case study was carried out in a clinical analysis laboratory located in the city of Rio Grande, where the AHP (Analytic Hierarchy Process) was used as an intervention tool. The development process consisted in three stages. The first one aimed at structuring the model, in which the hierarchy of criteria was defined. In the second step, the judgments were carried out and the relative weights for each criterion and subcriterion were calculated. Finally, the third step aimed at applying the model developed in a purchasing process. The model was tested in a selection process that involved the evaluation of three vendors of a laboratorial input, in order to identify which one met the demands of the organization. The result obtained with its use was considered satisfactory, this way, the model was approved by the manager who participated in the structuring process of the AHP hierarchy.